“Influencia de la temperatura y empaque en la calidad del aceite de sacha inchi (plukenetia volubilis L.) en capsulas y semillas ecotipo apangura de la provincia de lamas, durante almacenamiento” - Vanessa Sánchez Sánchez (2008)
This investigation work talks about the Sacha lnchi (Plukenetia volubilis L.) oil's physicist - chemistry characteristics, extracted from capsules and seeds stored during a period of tour months, with the intention of determining the influence of the environment temperature (28±2°C) and refrigeration temperature {16ºC) and the packing {sacks of polypropylene, jute and paper kraft) in the quality of above mentioned oil. Also, the almonds were evaluated seasonally to verify the best characteristics of the storage. This work was developed of the following way; storage in cold Chamber of the National institute of Agrarian innovation in Juan Guerra, preparation of samples for analysis in the Food Composition’s Laboratory of Agroindustry Engineering Faculty of the National University of San Martín - Tarapoto and the physicist - chemist analyses in Biotechnology’s Laboratory of the institute of investigations the Amazonia Peruana {lquitos). The analyses were carried out every month of stored, which allowed us to determine the best way of storing capsules and seeds under two storage systems; using a Complete Azar Design random with factorial arrangement of 2x3x2 (Presentation of the product * packing material* storage temperature) with 12 treatments in total, the results being analyzed by means of the analysis of variance {ANVA) followed by DUNCAN'S test(proof) by 5 % of probability, for the analysis of the difference between the averages. The sacha inchi in study belongs to the ecotipo Apangura and it was harvested of plots located in Pamashto's district, province of Lamas, Region San Martín. Operations were realized as dried of capsules, selection, released capsule, packed and stored; later were evaluated the physicist - chemistry quality parameters: color, dampness, acidity's index, peroxide's index, iodine's index, proteins and omega’s contents. let was realized the sensory analysis: flavor, crispy, rancidness and astringency of the almonds. The presentation of the product (capsules and seeds) demonstrated a significant difference in the measurement of color, but this did not influence in the oil's quality. In the presentation of the product, the capsules gave better results in the analyses, nevertheless the seeds also supported result inside the quality parameters. The material of jute packing showed an advantage with regard to the polypropylene and the paper Kraft, thanks to the low values in dampness, the acidity's index, the peroxide's index. By the other hand both storage temperatures determined variations in the value of the indexes of acidity and peroxide, turning out to be the temperature 16ºC the one that obtained minor values in these analyses. In case of the omegas and the iodol’s index, showed a trend of stability in the interaction of presentation and temperature, while remaining within the acceptable range of composition. The sensory evaluation indicated us trends of uniformity to us between(among) treatments, then in raw almonds the obtained values defined intense flavor to Sacha lnchi, without rancidness, very crocante and very astringent.